Contribution of Two-Dose Vaccination Toward the Reduction of COVID-19 Cases, ICU Hospitalizations and Deaths in Chile Assessed Through Explanatory Generalized Additive Models for Location, Scale, and Shape - Reyes, Humberto; Diethelm-Varela, Benjamin; Méndez, Constanza; Rebolledo-Zelada, Diego; Lillo-Dapremont, Bastián; Muñoz, Sergio R.; Bueno, Susan M.; González, Pablo A.; Kalergis, Alexis M. (Frontiers in Public Health, 2022)
ABSTRACT Objectives: To assess the impact of the initial two-dose-schedule mass vaccination campaign in Chile towards reducing adverse epidemiological outcomes due to SARS-CoV-2 infection. Methods: Publicly available epidemiological data ranging from 3 February 2021 to 30 September 2021 were used to construct GAMLSS models that explain the beneficial effect of up to two doses of vaccination on the following COVID-19-related outcomes: new cases per day, daily active cases, daily occupied ICU beds and daily deaths. Results: Administered first and second vaccine doses, and the statistical interaction between the two, are strong, statistically significant predictors for COVID-19-related new cases per day (R2 = 0.847), daily active cases (R2 = 0.903), ICU hospitalizations (R2 = 0.767), and deaths (R2 = 0.827). Conclusions: Our models stress the importance of completing vaccination schedules to reduce the adverse outcomes during the pandemic. Future work will continue to assess the influence of vaccines, including booster doses, as the pandemic progresses, and new variants emerge. Policy Implications: This work highlights the importance of attaining full (two-dose) vaccination status and reinforces the notion that a second dose provides increased non-additive protection. The trends we observed may also support the inclusion of booster doses in vaccination plans. These insights could contribute to guiding other countries in their vaccination campaigns.